Analisis Kinerja Karyawan Melalui Profesionalisme Kerja pada Family Business Tahu Gimbal Bu Yati di Ngaliyan Semarang - Aris Putra P.m; M, Devi Kurnia (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to determine the effect of work professionalism on employee performance at the Tahu Gimbal Bu Yati family business in Ngaliyan Semarang. The research method used is by conducting field observations and conducting interviews with business actors. The research results show that there are supporting factors and obstacles that have an impact on work professionalism and influence employee performance. The supporting factors consist of the division of job desks according to their fields; and easy communication. Meanwhile, inhibiting factors consist of the inability to run a jobdesk that is not an expert; and the emergence of family conflicts into business operations.